Evaluating the Role of Personality in Task Performance Across Varying Mental Workload Levels - Wiediartini; Udisubakti Ciptomulyono; Ratna Sari Dewi (Fakultas Teknik Universitas Pancasila, 2026)
Variations in task performance under different cognitive demands are often interpreted as indicating mental workload. Prior research has identified a link between personality and task performance. This study investigates whether personality traits influence performance under varying levels of mental workload in working memory tasks. Personality traits were assessed using the Eysenck Personality Inventory. Participants completed n-back tasks at three levels of difficulty to induce different levels of mental workload. The findings reveal significant differences in response times between extroverts and introverts across all task difficulties (p < 0.05), with introverts responding more quickly. A significant difference between neurotic and stable individuals emerged only at the medium difficulty level (p < 0.05), with stable individuals performing faster. Additionally, response times varied significantly across personality quadrants, with introvert-neurotic individuals showing faster responses at both low and high difficulty levels.